Etyka maklera w świetle polskiego prawa giełdowego okresu 1921–1939 - Marks, Bogusław Piotr (Annales. Etyka w Życiu Gospodarczym, 2011)
The stock exchange is regarded as one of the key institutions of market economy. Stockbrokers were a truly essential group of workers of the stock exchanges. It was on the level of their organization and professional ethics that depended the level of efficient functioning of this institution. The basic law regulations, orders and stock charters were traced in this paper as well as – essential for exchanges – different documents, which marked principles of stockbrokers’ activity. These principles were considered from the point of view of the ethical norms establishing the contemporary ethics of economic life. My special attention was concentrated on these principles of stockbrokers’ activities which concern the way of their appointing, rights as well as duties. „Ethical aspects” of stockbrokers’ activity on the Polish stock-exchanges were traced for the period from acceptation, in 1921, the first in independent Poland Act of exchanges organization to the outbreak of World War II. Except stock exchanges which were formed during the Period of the Partitions of Poland (in Warsaw and Lodz), and which resumed their activities after World War I, the new ones were created when Poland had regained its independence. Stock exchanges – except the above-mentioned – were organized in Cracow, Poznan, Vilnius and in Lvov. In initial period of the second Republic of Poland acted six commodities exchanges too. The comparatively quick unification of exchange law by the government of independent Poland was the expression of understanding the importance which was fulfilled (not only) in economy by the institution of stock exchange. In turn, issuing separate regulations for stockbrokers was proof of high position held by this group in the structure of the basic organs of a stock exchange.